Sex, Allergic Diseases and Omalizumab - Maria Maddalena Sirufo; Francesca De Pietro; Lia Ginaldi; Massimo De Martinis (Biomedicines, 2022)
Gender differences are increasingly emerging in every area of medicine including drug therapy; however, specific gender-targeted studies are infrequent. Sex is a fundamental variable, which cannot be neglected. When optimizing therapies, gender pharmacology must always be considered in order to improve the effectiveness and safety of the use of drugs. Knowledge of gender differences promotes appropriate use of therapies and greater health protection for both genders. Further development of gender research would make it possible to report on differences in the assimilation and response of the female organism as compared to the male, in order to identify potential risks and benefits that can be found between genders. Furthermore, a better understanding of sex/gender-related influences, with regard to pharmacological activity, would allow the development of personalized “tailor-made” medicines. Here, we summarize the state of knowledge on the role of sex in several allergic diseases and their treatment with omalizumab, the first biologic drug authorized for use in the field of allergology.